2019
DOI: 10.14744/nci.2019.54936
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile atherogenic indeces and their relation of epicardial fat thickness and carotid intima media thickness in Celiac disease

Abstract: OBJECTIVE:In this study, we aimed to investigate the presence of subclinical atherosclerosis by measuring epicardial fat thickness (EFT) and carotid intima–media thickness (cIMT), evaluate low-level inflammation with high-sensitivity C-reactive protein (hsCRP), and evaluate whether there is a relationship among lipid profile, atherogenic indices, and hsCRP with these subclinical atherosclerosis markers in patients with celiac disease (CD).METHODS:After exclusion and inclusion criteria were applied, 31 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…APOA1 is the major component of highdensity lipoprotein (HDL) which is strongly associated with coronary heart disease (CHD) 59,60 . Both low HDL levels and risk of CHD have been reported in CeD patients 61 . GO annotations of the second cluster includes drug metabolism, metal ion homeostasis, lipid and other molecules transportation.…”
Section: Discussionmentioning
confidence: 99%
“…APOA1 is the major component of highdensity lipoprotein (HDL) which is strongly associated with coronary heart disease (CHD) 59,60 . Both low HDL levels and risk of CHD have been reported in CeD patients 61 . GO annotations of the second cluster includes drug metabolism, metal ion homeostasis, lipid and other molecules transportation.…”
Section: Discussionmentioning
confidence: 99%
“…A high estradiol-to-testosterone ratio in the blood is associated with the elevation of triglycerides, LDL cholesterol, and total cholesterol levels but a decrease in HDL cholesterol levels [ 19 , 20 ]. These changes in the lipid profile may result in the onset of atherosclerosis [ 21 ], a condition defined by the accumulation of plaques in the arteries, and a major risk factor for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The ndings indicated that AIP is a reliable prognostic CVD biomarker in middle-aged adults (Onat et al 2010). Furthermore, AIP has been associated with validated biomarkers of subclinical atherosclerosis, such as the intima-media thickness of the carotid artery (cIMT), asymmetric dimethylarginine (ADMA), insulin resistance, the ratio of apolipoprotein B (apoB): apolipoprotein A-1 (apoA1), among others (Tongdee and Nimkuntod 2016;Cure et al 2018;Caliskan et al 2019;Fernandez-Macias et al 2019;Tecer et al 2019).…”
Section: Discussionmentioning
confidence: 99%